Real-time quantitative performance feedback during strength exercise improves motivation, competitiveness, mood, and performance. (September 2017) - Wilson, Kyle M.; Helton, William S.; de Joux, Neil R.; Head, James R.; Weakley, Jonathon J. S.
Providing quantitative feedback on performance in real-time appears to improve performance in a strength training context. Less is known about the associated effects on psychological variables. Fifteen rugby athletes performed a strength training exercise both with and without objective performance feedback provided in real-time. Feedback increased performance, consistent with previous research. Feedback also led to higher ratings of task competitiveness, state motivation, mood, and workload. These findings provide insight into possible underlying mechanisms responsible for the feedback's facilitative effects on performance. The findings also suggests that providing this type of feedback may have benefits within other industries, where attempts are frequently made to increase adherence to exercise and rehabilitation programs. This research carries important implications for the design and use of technology within both the sports science and healthcare industry.